Application of inductive coupling for wireless power transfer - Ibrahim Alhamrouni; M. Iskandar; Mohamed Salem; Lilik J. Awalin; Awang Jusoh; Tole Sutikno (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
Considering the massive development that took place in the past two decades, wireless power transfer has yet to show the applicability to be used due to several factors. This work focuses on determining the main parameters like, mutual inductance, and coupling coefﬁcient for a pair of helical coils for wireless power transfer applications. These parameters are important in designing and analyzing a wireless power transfer system based on the phenomenon of inductive/ resonant inductive coupling. Here presents a simple approach based on fundamental laws of physics for determining the coupled coil parameters for single layered helical coils. The results conducted by computer simulation which is MATLAB. Furthermore, this analysis is used to study the effect of change in coil diameter, mutual inductance coefficient and change in distance between coils on parameters like self and mutual inductance of coupled coils which is of great importance in Wireless Power Transfer applications. The research yielded promising results to show that wireless power transfer has huge possibility to solve many existing industrial problems.